We Underutilize the Leg Graft. Issue 4 (15th April 2016) - Allon, Michael
Abstract: Once hemodialysis patients have exhausted all option for a permanent vascular access in both upper extremities, they are often relegated at many dialysis centers to permanent catheter dependence with all its attendant complications, including infections, frequent dysfunction, and central vein stenosis. This commentary makes the case that thigh grafts are a far superior alternative to dialysis catheters in many of these patients. Technical graft failure may occur in some patients due to severe femoral artery calcification, but screening for calcification by ultrasound or computerized tomography can reduce the likelihood of a technical failure. Placement of a thigh graft may lead to critical lower extremity ischemia, but preoperative screening for peripheral vascular disease should minimize this possibility. Thigh grafts have comparable secondary patency to that obtained with upper extremity grafts. Finally, although the risk of infection is somewhat higher for thigh grafts than upper extremity grafts, it is still much lower than the risk of catheter‐related bacteremia. In summary, thigh grafts should be used much more frequently in patients without an option for an upper extremity access.